Developing and implementing a Radiotherapy Research Activity Assessment Tool (RAAT): a prospective feasibility study. Issue 3 (6th April 2016) - Goldsworthy, Simon; Roe, Benjamin; McGrail, Stuart; McCormack, Stephen; Walther, Julie
Abstract: Aim: Cancer research in the National Health Service has increased by 10·5% in 3 years since the formation of the National Cancer Research networks in 2000. The initial enthusiasm from clinical staffs to embark on a project has to be balanced against the implications of resources, costs and other developments. There is no standardised method to assess the impact of research projects on clinical practice. The aim of this project was to develop and implement a Radiotherapy Research Activity Assessment Tool (RAAT) to assess the feasibility of newly proposed projects within clinical settings. Methods and materials: A multi-step development method was used. The steps involved the principles of quality function deployment. The consecutive steps involved developing a user-friendly and replicable tool and would fit on one A4 page. The process involved multi-professionals and patients throughout the design process. The tool was preliminary tested on usability among eight stakeholders on a ten-point scale (1=poor; 10=very good). Percentage agreement was evaluated at 6 month post initial RAAT assessment scoring by the seven multi-disciplinary team (MDT) members. Findings: The RAAT was developed in an e-form available in Microsoft Excel. The tool scored a mode of 6 for usability. Interrater reliability testing between the radiotherapy MDT resulted in 88% agreement. The RAAT seems to be feasible in clinical practice, and provide a framework to guide the decision-making process. The study calls for further testing of usability and review of long-term implications on all stakeholders.